Deployment Opportunities for Space Photovoltaics and the Prospects for Perovskite Solar Cells. Issue 3 (5th November 2021) - Ho‐Baillie, Anita W. Y.; Sullivan, Hamish G. J.; Bannerman, Thomas A.; Talathi, Harsh. P.; Bing, Jueming; Tang, Shi; Xu, Alan; Bhattacharyya, Dhriti; Cairns, Iver H.; McKenzie, David. R.
Abstract: The rapid progress in space exploration, mining, and tourism has been fuelled by both public and private sector investments. The latter has led to the need to reduce manufacturing and launch cost of space hardware to create a competitive and sustainable space economy. A major step in making space accessible is to develop affordable power systems for "commercial space" use. Photovoltaics has in the past and will in the future be a key component. Metal halide perovskite solar cells show the greatest potential of all emerging technologies for low‐cost space photovoltaics. They have demonstrated the highest rate of power conversion efficiency improvement. Compared to the triple junction III–V compound semiconductor cells commonly used for space applications, perovskite cells have a higher power to weight ratio and are significantly cheaper to be manufactured. They have high radiation tolerance and can be fabricated onto flexible substrates for expand‐on‐demand solar panels. This paper outlines the major space markets for photovoltaics, and research and development opportunities for perovskite space solar cells in the context of their recent progress. Abstract : This paper begins with a survey of potential markets for space photovoltaics. Cost savings of deploying perovskite as opposed to III–V solar cells are then estimated. The second part of the paper discusses the challenges faced by perovskite cells for space applications and a critical review of research progress to date. Future research directions are given for each challenge.